Bridge waterproof anti-cracking paste and construction method thereof

CN122960085APending Publication Date: 2026-10-23KESHUN WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611044883.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

一旦防水层局部破损,腐蚀介质长驱直入,桥面板钢筋锈蚀风险急剧上升

Benefits of technology

[0011]与现有三层结构SBS改性沥青防水卷材相比,本发明提供的桥面防水抗裂贴具有以下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of road and bridge engineering, and discloses a bridge waterproof and anti-cracking patch and a construction method thereof. The bridge waterproof and anti-cracking patch contains a core rubber layer, and the core rubber layer comprises an anti-aging rubber layer, a pre-impregnated polyester tire layer, a functional rubber layer and a hot-melt self-leveling rubber layer which are sequentially stacked. The application provides a bridge waterproof and anti-cracking patch which has both a crack active following filling function and a chemical corrosion prevention function, can actively flow into micro cracks for plugging during hot-melt construction, continuously captures chloride ions and neutralizes acid-alkali corrosion media during a service period, and realizes double active protection of 'physical following + chemical protection'.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road and bridge engineering technology, specifically to a bridge deck waterproof and crack-resistant adhesive and its construction method. Background Technology

[0002] A waterproof bonding layer is required between the cement concrete bridge deck and the asphalt pavement layer to serve three main functions: waterproofing, bonding, and stress absorption. Currently, there are two main types of commonly used technical solutions: The first type is a waterproof bonding layer coating, which involves spraying or rolling an SBS-modified asphalt-based, polyurethane-based, or epoxy resin-based waterproof coating onto the bridge deck to form a continuous waterproof membrane. This solution is simple to construct, but it cannot track cracks in the bridge deck; once the bridge deck cracks, the coating will tear.

[0003] The second type is pre-formed waterproof membrane, which uses factory-prefabricated SBS modified bitumen waterproof membrane. It is generally a single-layer or double-layer structure, laid on the bridge deck using hot-melt or self-adhesive methods. The membrane may be reinforced with a polyester or fiberglass base. It typically consists of a three-layer structure: an upper surface layer (high softening point modified bitumen), a base layer (polyester or fiberglass mesh), and a lower surface layer (low softening point modified bitumen). This type of membrane has some crack resistance, but it mainly relies on the base layer to passively resist crack propagation; it cannot actively fill existing micro-cracks and does not possess active chemical corrosion protection.

[0004] For example, CN115231857A discloses a method for improving the aging performance of asphalt pavement materials through layered modification. This prior art provides a method for improving the aging performance of asphalt pavement materials through layered modification. Based on the gradient aging behavior characteristics of different layers of asphalt pavement materials, it designs layered anti-aging measures for different layers, targeting the factors and aging mechanisms that cause aging of asphalt materials in each layer. This aims to address the gradient aging behavior characteristics, reduce the production and construction costs of road surface materials, and obtain uniformly aged old materials at the end of the pavement's service life, creating favorable conditions for the recycling of old materials.

[0005] However, the aforementioned existing technology has the following drawbacks: Unable to actively follow and fill cracks: Although the lower layer of the existing waterproofing membrane has a low softening point, it remains solid after construction and cannot effectively flow into the existing micro-cracks (width <0.5mm) in the bridge deck for filling and sealing. Under load and temperature, the cracks repeatedly open and close, tearing the waterproofing layer from the bottom, resulting in "zero-elongation fracture".

[0006] Lacks active chemical protection capability: Existing waterproof membranes have a single function, relying solely on the physical barrier of the asphalt layer itself for waterproofing. They cannot actively resist the chemical corrosion caused by the penetration of snow melting salt (chlorides) in winter, nor can they neutralize the erosion of bridge deck concrete by corrosive media such as acid rain.

[0007] The separation of corrosion protection and waterproofing functions: In actual engineering projects, waterproof membranes only serve to block water, while corrosion prevention relies on the concrete protective layer of the bridge deck and the rust inhibitor for the reinforcing steel. The two lack synergy. Once the waterproof layer is partially damaged, corrosive media can penetrate freely, and the risk of corrosion of the bridge deck's reinforcing steel increases dramatically. Summary of the Invention

[0008] The purpose of this invention is to provide a bridge deck waterproof and crack-resistant tape that combines the functions of actively following and filling cracks with chemical corrosion protection. It can actively flow into micro-cracks to seal them during hot-melt construction, and at the same time continuously capture chloride ions and neutralize acid and alkali corrosive media during its service life, achieving dual active protection of "physical following + chemical protection".

[0009] To achieve the above objectives, a first aspect of the present invention provides a bridge deck waterproof and crack-resistant adhesive tape, which includes a core adhesive layer, the core adhesive layer comprising an aging-resistant adhesive layer, a pre-impregnated polyester layer, a functional adhesive layer, and a hot-melt self-leveling adhesive layer stacked sequentially. The softening point of the aging-resistant adhesive layer is 90-110℃; The softening point of the functional adhesive layer is 80-95℃, the penetration at 25℃ is 50-70 / 0.1mm, and the elastic recovery rate at 25℃ is ≥85%. The softening point of the hot-melt self-leveling adhesive layer is 65-80℃, the penetration at 25℃ is 80-110 / 0.1mm, the melt viscosity at 160℃ is ≤400 mPa·s, and the melt viscosity at 180℃ is ≤200 mPa·s.

[0010] A second aspect of the present invention provides a method for constructing the bridge deck waterproof and crack-resistant adhesive tape described in the first aspect, the method comprising: Step 1: Lay the bridge deck waterproof and crack-resistant tape on the bridge deck. Use a flame torch to heat the lower surface of the bridge deck waterproof and crack-resistant tape, so that the hot melt self-leveling adhesive layer on the lower surface is heated to 140-160℃ and melts into a liquid state. While it is hot, use a pressure roller to roll it, so that the adhesive of the hot melt self-leveling adhesive layer on the lower surface actively flows into the micro-cracks of the base surface under pressure. Step 2: Pour heated asphalt mixture onto the upper surface of the bridge deck waterproof and crack-resistant tape to melt the aging-resistant adhesive layer on the upper surface of the tape. Step 3: Use a road roller to compact and shape the material, so that the aging-resistant rubber layer on the upper surface of the bridge deck waterproof and crack-resistant tape is fused with the heated asphalt mixture. After cooling and setting, the construction is completed.

[0011] Compared with existing three-layer SBS modified bitumen waterproof membranes, the bridge deck waterproof and crack-resistant tape provided by this invention has the following advantages: 1. Active Crack-Following Filling Capability: Through the low softening point and high fluidity design of the lower surface hot-melt self-leveling adhesive layer, it becomes liquid during hot-melt construction and actively flows into the micro-cracks of the bridge deck under rolling pressure. After cooling, it forms a "micro-anchoring" interlocking structure. Although the lower layer of existing roll materials has a low softening point, it lacks a fluidity design and can only passively cover the surface of cracks, unable to penetrate deep into the cracks for sealing.

[0012] 2. Gradient softening point design concept: The softening point of each rubber layer decreases layer by layer from top to bottom (90-110℃→80-95℃→65-80℃). During hot melt construction, the lower layer melts and flows first while the upper layer remains stable, which solves the problem of "simultaneous softening of the upper and lower layers and structural collapse" in traditional roll material hot melt construction.

[0013] 3. Integrated Functions: The product integrates six functions, including waterproofing, bonding, stress absorption, crack following and filling, acid and alkali neutralization, and chloride ion capture, into a single product. This reduces the construction steps and material types required for bridge deck pavement systems, thereby lowering overall costs and maintenance difficulty. Detailed Implementation

[0014] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0015] As mentioned above, the first aspect of the present invention provides a bridge deck waterproof and crack-resistant adhesive tape, which includes a core adhesive layer, the core adhesive layer comprising an aging-resistant adhesive layer, a pre-impregnated polyester layer, a functional adhesive layer, and a hot-melt self-leveling adhesive layer stacked sequentially. The softening point of the aging-resistant adhesive layer is 90-110℃; The softening point of the functional adhesive layer is 80-95℃, the penetration at 25℃ is 50-70 / 0.1mm, and the elastic recovery rate at 25℃ is ≥85%. The softening point of the hot-melt self-leveling adhesive layer is 65-80℃, the penetration at 25℃ is 80-110 / 0.1mm, the melt viscosity at 160℃ is ≤400 mPa·s, and the melt viscosity at 180℃ is ≤200 mPa·s.

[0016] Preferably, based on the total mass of material A forming the functional rubber layer, material A contains: 40-50 wt% of 90# petroleum asphalt, 6-10 wt% of star-shaped SBS, 14-25 wt% of softening oil, and 4-10 wt% of rubber powder.

[0017] Preferably, based on the total mass of material A forming the functional adhesive layer, material A further contains: 1-3 wt% acid-base buffer, 2-5 wt% chloride ion scavenger, 0.3-0.6 wt% coupling agent, 0.3-0.5 wt% antioxidant, and 10-18 wt% inorganic filler.

[0018] In this invention, the functional adhesive layer provided by this invention is the core functional layer for chemical corrosion protection. It carries two functional additives, acid-base buffer and chloride ion scavenger, and has high elasticity, which can follow the opening and closing of cracks.

[0019] Preferably, the acid-base buffer is selected from at least one of cobalt borate and cobalt naphthenate.

[0020] In a preferred embodiment, the chloride ion scavenger is selected from at least one of magnesium aluminum layered bimetallic hydroxide, calcium aluminum layered bimetallic hydroxide, and synthetic zeolite.

[0021] According to a specific embodiment, the functional adhesive layer is prepared by the following method: first, a first part of softening oil is premixed with an acid-base buffer and ground with a three-roll mill to obtain slurry I with a particle size ≤10μm; then, a second part of softening oil, a chloride ion scavenger, and nano-calcium carbonate are stirred and premixed to form slurry II. Heat 90# petroleum asphalt to 160-170℃, add star-shaped SBS and stir for 110-130 minutes. Then, put the slurry I, the slurry II, the rubber powder, the coupling agent, the antioxidant, the inorganic filler and the remaining softening oil into the mixing tank and stir to mix. Keep it at 175-185℃ for 2-4 hours, and then coat it to form a functional rubber layer.

[0022] The bridge deck waterproofing and crack-resistant tape provided by this invention has a dual-layer active chemical protection capability. For the first time, two functional additives, an acid-base buffer and a chloride ion scavenger, are introduced into the bridge deck waterproofing and crack-resistant tape, forming a complementary and synergistic chemical protection system. Existing roll materials rely solely on the passive physical barrier of the asphalt layer, lacking active chemical protection capabilities.

[0023] More preferably, the acid-base buffer is cobalt borate; the chloride ion scavenger is magnesium aluminum layered bimetallic hydroxide and / or calcium aluminum layered bimetallic hydroxide.

[0024] The inventors discovered that during service, externally intruding acid rain or alkaline media are first rapidly neutralized by cobalt borate in the functional adhesive layer through the amphoteric adsorption of borate groups, maintaining a neutral chemical environment in the adhesive layer. Chloride ions (mainly from de-icing salt) are captured and locked by the layered bimetallic hydroxides in the functional adhesive layer through interlayer ion exchange, while nitrite ions (NO3) pre-intercalated between the layers of the layered bimetallic hydroxides are also neutralized. 2-The ions are exchanged and released, migrating to the surface of the reinforcing steel to form a passivating protective film, inhibiting steel corrosion. Cobalt borylate and layered bimetallic hydroxides complement each other—the former primarily targets acid / alkali media, while the latter primarily targets chloride ions, forming a synergistic chemical protection system covering all pH levels and all ions.

[0025] Preferably, the coupling agent is selected from at least one of silane coupling agent KH-550, silane coupling agent KH-560, and titanate coupling agent.

[0026] In a preferred embodiment, the material B forming the hot-melt self-leveling compound layer is based on the total mass of the material B, which contains: 45-55 wt% of 70# petroleum asphalt, 2-7 wt% of linear SBS, 18-30 wt% of softening oil, and 3-6 wt% of rubber powder.

[0027] Preferably, based on the total mass of material B forming the hot melt self-leveling adhesive layer, material B further contains: 2-5 wt% thickener, 3-8 wt% binder, 0.3-0.5 wt% antioxidant, and 5-12 wt% inorganic filler.

[0028] In this invention, the hot-melt self-leveling adhesive layer provided is a key layer for hot-melt construction. Under flame heating, it first melts and exhibits low viscosity and high fluidity, allowing it to actively flow into the micro-cracks of the bridge deck. The lower surface of this layer is covered with a fusible PE film, which does not require peeling during construction; the PE film is directly fused with the hot-melt self-leveling adhesive layer by flame heating.

[0029] Preferably, the thickener is selected from at least one of microcrystalline wax, Fischer-Tropsch wax, and polyethylene wax.

[0030] In a preferred embodiment, the binder is selected from at least one of C5-C9 copolymer petroleum resin, hydrogenated terpene resin, and rosin resin.

[0031] According to a specific embodiment, the hot-melt self-leveling compound layer is prepared by the following method: petroleum asphalt is heated to 150-160℃, linear SBS is added and stirred for 110-130 minutes, then softening oil, rubber powder, thickener, binder, antioxidant and inorganic filler are added, and the mixture is stirred and mixed at 175-185℃ and kept at the temperature for 2-4 hours. Then the temperature is lowered to 160-165℃, and the mixture is coated and molded to obtain the hot-melt self-leveling compound layer.

[0032] Preferably, based on the total mass of material C forming the aging-resistant rubber layer, material C contains: 50-63 wt% of 90# petroleum asphalt, 8-15 wt% of linear SBS, 7-14 wt% of softening oil, and 10-18 wt% of rubber powder.

[0033] Preferably, based on the total mass of material C forming the aging-resistant adhesive layer, material C further contains: 0.2-0.6 wt% ultraviolet absorber, 0.3-0.8 wt% antioxidant, and 1-4 wt% inorganic filler.

[0034] Preferably, in the material C forming the aging-resistant adhesive layer, the linear SBS can be replaced by linear SIS or linear SEBS.

[0035] In a preferred embodiment, the ultraviolet absorber is selected from at least one of UV-326 and UV-328.

[0036] According to a specific embodiment, the aging-resistant rubber layer is prepared by the following method: 90# petroleum asphalt is heated to 160-170℃, linear SBS is added and stirred for 60-120 minutes, then softening oil, rubber powder, ultraviolet absorber, antioxidant and inorganic filler are added, and the mixture is stirred and mixed at 170-180℃ and kept at the temperature for 2-4 hours. Finally, the temperature is lowered to 160-165℃ and discharged. After coating and molding, the aging-resistant rubber layer is obtained.

[0037] Preferably, the prepreg polyester layer is obtained by impregnating the polyester layer in a prepreg until saturated.

[0038] Preferably, 0.7-0.9 kg of prepreg is impregnated per square meter of polyester tire.

[0039] Preferably, the immersion is carried out in a hot immersion bath at a temperature of 160-180°C for 2-5 seconds.

[0040] Preferably, the basis weight of the polyester tire is 180-250 g / m². 2 .

[0041] Preferably, based on the total mass of the prepreg, the prepreg contains: 48-65 wt% of 90# petroleum asphalt and 33%-45% of 10# asphalt.

[0042] Preferably, based on the total mass of the prepreg, the prepreg further contains: 0.3-0.5 wt% antioxidant and 4-10 wt% inorganic filler.

[0043] Preferably, the softening oil is selected from at least one of aromatic oils and naphthenic oils.

[0044] More preferably, the aromatic oil contains ≥50wt% aromatic hydrocarbons.

[0045] More preferably, the pour point of the naphthenic oil is ≤-10℃.

[0046] Preferably, the average particle diameter of the adhesive powder is ≤180μm.

[0047] In a preferred embodiment, the antioxidant is selected from at least one of antioxidant 1010 and antioxidant 1076.

[0048] Preferably, the inorganic filler is selected from at least one of nano-calcium carbonate and carbon black N330.

[0049] In a preferred embodiment, the average particle diameter of the inorganic filler is 150-350 nm.

[0050] In preferred embodiments, the thickness of the aging-resistant adhesive layer is 1.5-2 mm; the thickness of the prepreg polyester layer is 0.8-1.2 mm; the thickness of the functional adhesive layer is 1-2 mm; and the thickness of the hot-melt self-leveling adhesive layer is 0.8-1.5 mm, preferably 1 mm.

[0051] In a preferred embodiment, the thickness of the core adhesive layer is 4-7 mm, preferably 5 mm.

[0052] Preferably, the surface of the core adhesive layer is covered with a polyethylene film layer. The bridge deck waterproof and crack-resistant tape provided by the present invention features a peel-free design with a fusible polyethylene film (PE film). Both the upper and lower surfaces of the core adhesive layer are covered with a fusible PE film, eliminating the need for manual peeling during construction. The PE film is directly melted and fused with the adhesive by heating with a flame torch, reducing construction steps and peeling waste, and avoiding damage to the adhesive layer during peeling.

[0053] As mentioned above, a second aspect of the present invention provides a method for constructing the bridge deck waterproof and crack-resistant adhesive tape described in the first aspect, the method comprising: Step 1: Lay the bridge deck waterproof and crack-resistant tape on the bridge deck. Use a flame torch to heat the lower surface of the bridge deck waterproof and crack-resistant tape, so that the hot melt self-leveling adhesive layer on the lower surface is heated to 140-160℃ and melts into a liquid state. While it is hot, use a pressure roller to roll it, so that the adhesive of the hot melt self-leveling adhesive layer on the lower surface actively flows into the micro-cracks of the base surface under pressure. Step 2: Pour heated asphalt mixture onto the upper surface of the bridge deck waterproof and crack-resistant tape to melt the aging-resistant adhesive layer on the upper surface of the tape. Step 3: Use a road roller to compact and shape the material, so that the aging-resistant rubber layer on the upper surface of the bridge deck waterproof and crack-resistant tape is fused with the heated asphalt mixture. After cooling and setting, the construction is completed.

[0054] Preferably, the temperature of the flame melting is 1800-2000℃, and the nozzle of the flame gun is 20-30cm away from the lower surface of the bridge deck waterproof and crack-resistant tape.

[0055] Preferably, the pressure is applied by rolling with a heavy steel roller weighing 10-15 kg.

[0056] Preferably, the temperature of the heated asphalt mixture is >130°C.

[0057] In this invention, during construction, the aging-resistant adhesive layer provided by this invention is bonded to the asphalt layer to be laid above, and is simultaneously exposed to construction flames and ultraviolet radiation during service life, thus exhibiting a high softening point and excellent aging resistance.

[0058] Preferably, step 2 has a construction delay time compared to step 1, which is 15 to 30 days according to the construction period.

[0059] According to one specific embodiment, the construction method of the bridge deck waterproofing and crack-resistant tape includes: S1: Clean the bridge deck. Cracks wider than 1mm should be filled until smooth.

[0060] S2: Lay the bridge deck waterproof and crack-resistant tape on the bridge deck, with a long side overlap width ≥ 80mm and a short side overlap width ≥ 100mm; the polyethylene film on the underside of the bridge deck waterproof and crack-resistant tape does not need to be peeled off. S3: Use a liquefied gas flame torch to bake the polyethylene film on the lower surface of the bridge deck waterproof and crack-resistant adhesive. The flame temperature is 1800-2000℃, and the nozzle of the torch is 20-30cm away from the lower surface. Move it back and forth, and at the same time, the hot melt self-leveling adhesive layer on the lower surface is heated to 140-160℃ and completely melts into a liquid state. S4: While still hot, use a 10-15kg heavy steel roller to roll the bridge deck waterproof and crack-resistant adhesive at least 3 times, so that the molten self-leveling adhesive on the lower surface actively flows in under pressure and fills the micro-cracks in the bridge deck with a width of ≤0.5mm.

[0061] S5: Allow to cool naturally to room temperature, and the molten adhesive will solidify within the micro-cracks, completing the application of the bridge deck waterproof and crack-resistant tape; S6: Pour heated asphalt mixture onto the upper surface of the bridge deck waterproof and crack-resistant tape. The aging-resistant rubber layer on the upper surface of the bridge deck waterproof and crack-resistant tape melts under the heat of the heated asphalt mixture. Then, use a road roller to compact and shape it, so that the upper surface of the bridge deck waterproof and crack-resistant tape and the asphalt mixture are thermally fused together. The asphalt layer is then laid on the upper surface of the bridge deck waterproof and crack-resistant tape. After cooling and setting, the construction is completed.

[0062] The bridge deck waterproofing and crack-resistant tape provided by this invention has the ability to actively track cracks during construction. After analyzing the reasons, the inventors speculate that the possible mechanism is as follows: During hot-melt construction, the self-leveling adhesive layer on the lower surface is heated and becomes a low-viscosity liquid. Under rolling pressure, it flows into the micro-cracks of the bridge deck and forms a "micro-anchoring" interlocking structure after cooling. When the cracks in the bridge deck open or close due to load or temperature changes, the flexible adhesive extends or retracts accordingly. The stress is absorbed and buffered by the functional adhesive layer (high elasticity) above, and the polyester layer provides tensile strength to prevent through-cracks.

[0063] The present invention will be described in detail below through embodiments. Unless otherwise specified, all instruments and materials used in the following embodiments are commercially available products.

[0064] In the following examples, unless otherwise specified, room temperature / normal temperature refers to 25±2℃.

[0065] In the following examples, unless otherwise specified, a part refers to a portion by weight, where each portion by weight is 1g.

[0066] 90# petroleum asphalt: This is road petroleum asphalt, purchased from Jingbo Petrochemical.

[0067] 70# petroleum asphalt: This is road petroleum asphalt, purchased from Jingbo Petrochemical.

[0068] Star-shaped SBS: Grade Li Changrong 3411, purchased from Dongguan Yucheng Plastics Co., Ltd.

[0069] Linear SBS: Grade Li Changrong 3501, purchased from Dongguan Zhangmutou Hengtai Plastic Raw Materials Business Department.

[0070] Aromatic oil: Aromatic hydrocarbon content of 60wt%, flash point of 230℃, purchased from Shandong Xinglong New Materials Co., Ltd.

[0071] Naphthenic oil: pour point -16℃, purchased from Shandong Zhuyou Lubrication Technology Co., Ltd.

[0072] Rubber powder: Waste tire rubber powder, 80 mesh (purity 99wt%), purchased from Shengfei Mineral Products Processing Plant in Lingshou County.

[0073] Magnesium-aluminum layered bimetallic hydroxide: purity 99 wt%, purchased from Xi'an Ruixi Biotechnology Co., Ltd.

[0074] Calcium-aluminum layered bimetallic hydroxide: purity 99 wt%, grade calcium-aluminum hydrotalcite, purchased from Shandong Jinshengtai Chemical Co., Ltd.

[0075] Silane coupling agent KH-550: purchased from Jining Tangyi Chemical Co., Ltd.

[0076] Microcrystalline wax: purity 99wt%, CAS number 8001-75-0, purchased from Shanghai Baoyang Baoxin Biotechnology Co., Ltd.

[0077] Fischer-Tropsch wax: 100 wt% purity, purchased from Wuhan Xindongyi Chemical Co., Ltd.

[0078] Polyethylene wax: 95wt% purity, grade YY-613A, purchased from Guangzhou Yuantai New Materials Co., Ltd.

[0079] C5-C9 copolymer petroleum resin: purity 99wt%, density 0.95g / cm³ 3 Purchased from Guangzhou Binlong Chemical Co., Ltd.

[0080] Hydrogenated terpene resin: CAS No. 106168-39-2, purchased from Jiangsu Bosite Chemical Technology Co., Ltd.

[0081] Rosin resin: density 1.073 g / cm³ 3 Purchased from Jinan Wanhui New Materials Co., Ltd.

[0082] UV-326, UV-328, Antioxidant 1010, and Antioxidant 1076 were purchased from Jiangsu Xinluda Polymer Materials Co., Ltd.

[0083] Nano-calcium carbonate: with an average particle diameter of 200 nm, purchased from Qinghe County Chaotai Metal Materials Co., Ltd.

[0084] Carbon black N330: model number JYS15451, purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0085] Polyester tire: 250g / m² 2 The product is a long-fiber polyester tire, purchased from Shouguang Fada Textile Co., Ltd.

[0086] Polyethylene film (PE film): Model SBS PE film, thickness 0.008mm, purchased from Cangzhou Zhaoyang Paper & Plastic Packaging Co., Ltd.

[0087] Example 1 (1) Preparation of aging resistant rubber layer: Petroleum asphalt is heated to 165°C, linear SBS is added and stirred for 90 minutes until completely dissolved, then softening oil, rubber powder, ultraviolet absorber, antioxidant and inorganic filler are added, and the mixture is stirred and mixed evenly at 175°C and kept warm for 3 hours. Finally, the temperature is lowered to 160°C and discharged. After coating and molding, the aging resistant rubber layer is obtained.

[0088] (2) Preparation of prepreg polyester layer: The prepreg was prepared according to the formula shown in Table 1. The polyester layer (250 g / m²) was then prepared. 2 The prepreg is heated in a hot dip tank at 170°C for 3 seconds, and the amount of adhesive is controlled by the extrusion rollers to fully saturate the tire base.

[0089] (3) Preparation of functional adhesive layer: Take 5 parts of the 20 parts softening oil in the formula and premix it with 2 parts acid-base buffer. Grind it with a three-roll mill until the particle size is ≤10μm into slurry I; then take 5 parts and add 3 parts chloride ion scavenger and 13.1 parts nano calcium carbonate together. Stir and premix to form slurry II. Petroleum asphalt was heated to 165°C, star-shaped SBS was added and stirred for 120 minutes until completely dissolved. Then, slurry I, slurry II, rubber powder, coupling agent, antioxidant, inorganic filler and the remaining 10 parts of softening oil were added to the mixing tank and mixed. The mixture was kept at 180°C for 3 hours and then coated to form a functional rubber layer.

[0090] (4) Preparation of hot melt self-leveling compound layer: Heat petroleum asphalt to 155°C, add linear SBS and stir for 120 min until completely dissolved, then add softening oil, rubber powder, thickener, binder, antioxidant and inorganic filler, stir and mix evenly at 180°C and keep warm for 3 h, then cool down to 160°C, and coat and form to obtain hot melt self-leveling compound layer.

[0091] (5) Covering with polyethylene film layer: Cover the upper and lower surfaces of the prepared core adhesive layer with polyethylene film (PE film), and then press and roll it up to obtain the finished bridge deck waterproof and crack-resistant tape.

[0092] Examples 2-5 The same process as in Example 1 was used, except that the types and amounts of raw materials were different, as shown in Table 1.

[0093] Table 1

[0094] Comparative Example 1 The process is the same as in Example 1, except that no softening point gradient is formed between the softening points of each layer. Specifically: Aging-resistant rubber layer: The amount of linear SBS was adjusted from 10 parts to 6 parts, and the amount of softening oil was adjusted from 12 parts to 16 parts; Functional rubber compound layer: The amount of star-shaped SBS was adjusted from 8 parts to 5 parts, the amount of softening oil was adjusted from 20 parts to 25 parts, and the amount of inorganic filler was adjusted from 13.1 parts to 11.1 parts. Hot melt self-leveling compound layer: The amount of linear SBS is adjusted from 4 parts to 7 parts, the amount of softening oil is adjusted from 25 parts to 18 parts, and the amount of inorganic filler is adjusted from 8 parts to 12 parts. The remaining components and dosages are the same as in Example 1.

[0095] Comparative Example 2 The same procedure as in Example 1 was used, except that... Hot melt self-leveling compound layer: The amount of softening oil is adjusted from 25 parts to 15 parts, the amount of 70# petroleum asphalt is adjusted from 50 parts to 55 parts, the amount of rubber powder is adjusted from 5 parts to 2 parts, and the amount of inorganic filler is adjusted from 8 parts to 16 parts. The remaining components and dosages are the same as in Example 1.

[0096] Comparative Example 3 The same procedure as in Example 1 was used, except that... Functional rubber layer: The 90# petroleum asphalt was reduced from 45 parts to 35 parts, and an additional 10 parts of 10# asphalt were added (the total asphalt content remained at 45 parts). The remaining components and dosages are the same as in Example 1.

[0097] The thickness, softening point, penetration, elastic recovery rate, melt viscosity, and corrosion current density of each layer in the bridge deck waterproof and crack-resistant adhesive prepared in the above embodiments and comparative examples were tested. The test methods are as follows: Thickness: Tested in accordance with GB / T 328.4-2007 "Test Methods for Waterproofing Membranes - Part 4: Thickness and Mass per Unit Area of ​​Bituminous Waterproofing Membranes".

[0098] Softening point (ring and ball method): Tested according to GB / T 4507-2014 "Determination of softening point of bitumen (ring and ball method)". Penetration: Tested according to GB / T 4509-2010 "Asphalt Penetration Test Method".

[0099] Elastic recovery rate: Tested in accordance with the provisions of T0662 in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0100] Melt viscosity: The test was conducted using a Brookfield rotational viscometer in accordance with the provisions of T0625 in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0101] The method for testing corrosion current density is as follows: 1) Preparation of concrete test blocks: C40 concrete cube specimens with dimensions of 150mm×150mm×150mm were used. During specimen casting, a 10mm diameter, 200mm long HRB400 steel bar was pre-embedded in the center of the specimen. One end of the steel bar protruded approximately 50mm from the top surface of the specimen for electrochemical testing connection, while the remaining part was completely embedded in the concrete. The protective layer thickness of the steel bar (i.e., the distance from the surface of the steel bar to the top surface of the specimen) was 25mm. After the specimens were cast, they were cured for 28 days under standard curing conditions (temperature 20±2℃, relative humidity ≥95%).

[0102] 2) Laying of waterproof and crack-resistant tape on bridge deck: Take the bridge deck waterproof and crack-resistant tape prepared in each embodiment and comparative example, cut it into samples with a size of 200mm×200mm, peel off the PE film on the lower surface of the sample, and apply it to the top surface of the concrete test block (i.e. the side of the steel reinforcement protective layer) by hot melting method so that the crack-resistant tape completely covers the top surface of the test block.

[0103] 3) Alternate soaking: Concrete test blocks coated with bridge deck waterproofing and crack-resistant tape were alternately immersed in a salt solution containing 3.5 wt% chloride ions (simulating seawater / snow melt brine) and an acidic solution with pH=4.5 (simulating acid rain), alternating every 24 hours for 30 days. During the immersion, the crack-resistant tape on the top surface of the test block was completely submerged below the liquid surface.

[0104] 4) Corrosion current density test: After soaking, the concrete specimen was removed. Using the embedded steel reinforcement as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the auxiliary electrode, a three-electrode system was employed to measure the corrosion current density (μA / cm²) of the steel reinforcement on an electrochemical workstation. 2 The lower the corrosion current density, the better the chemical protection capability of the bridge deck waterproofing and crack-resistant tape for the reinforcing steel.

[0105] The test results are shown in Table 2.

[0106] Table 2

[0107] Application example: Construction method of waterproof and crack-resistant tape for bridge decks S1: Bridge deck treatment. Clean the bridge deck and ensure it is dry and free of standing water; for cracks wider than 1mm, fill the cracks until they are smooth.

[0108] S2: Laying and positioning. The bridge deck waterproof and crack-resistant tape prepared in the example is initially laid on the bridge deck, with a long side overlap width ≥80mm and a short side overlap width ≥100mm; the fusible PE film on the underside of the bridge deck waterproof and crack-resistant tape does not need to be peeled off.

[0109] S3: Flame Melting. Use a liquefied gas flame torch (flame temperature approximately 1900℃) to heat the PE film on the underside of the bridge deck waterproof and crack-resistant adhesive. Keep the torch nozzle 25cm away from the underside of the adhesive and move it back and forth at a uniform speed. The PE film on the underside melts upon heating, and simultaneously, the self-leveling adhesive layer on the underside melts completely at 150℃, becoming liquid.

[0110] S4: Compact and follow. While still hot, use a pressure roller (13kg) to roll the bridge deck waterproof and crack-resistant adhesive on the upper surface at least 3 times. This allows the molten self-leveling adhesive on the lower surface to actively flow into and fill the micro-cracks in the bridge deck with a width of ≤0.5mm under pressure, squeezing out the air between layers and forming a "micro-anchoring" interlocking.

[0111] S5: Cooling and Shaping. Allow to cool naturally to room temperature, and the molten adhesive will solidify within the micro-cracks in the bridge deck.

[0112] S6: Paving the asphalt layer. After step S5, at an interval of 15 days, hot-mix asphalt mixture is poured onto the surface of the bridge deck waterproofing and crack-resistant tape. The aging-resistant rubber layer on the surface of the bridge deck waterproofing and crack-resistant tape melts under the heat of the hot-mix asphalt mixture. Then, a road roller is used to compact the asphalt mixture, so that the surface of the bridge deck waterproofing and crack-resistant tape and the asphalt mixture are thermally fused together. The asphalt layer is then laid on the surface of the bridge deck waterproofing and crack-resistant tape. After cooling and setting, the construction is complete.

[0113] As can be seen from the above examples, the present invention provides a bridge deck waterproof and crack-resistant tape that combines the functions of actively following and filling cracks and chemical corrosion prevention. It can actively flow into the micro-cracks of the bridge deck for sealing during hot-melt construction, and at the same time continuously capture chloride ions and neutralize acid and alkali corrosive media during the service life, achieving dual active protection of "physical following + chemical protection".

[0114] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A bridge deck waterproof and crack-resistant adhesive, characterized in that, The bridge deck waterproof and crack-resistant tape contains a core adhesive layer, which includes an aging-resistant adhesive layer, a pre-impregnated polyester layer, a functional adhesive layer, and a hot-melt self-leveling adhesive layer stacked in sequence. The softening point of the aging-resistant adhesive layer is 90-110℃; The softening point of the functional adhesive layer is 80-95℃, the penetration at 25℃ is 50-70 / 0.1mm, and the elastic recovery rate at 25℃ is ≥85%. The softening point of the hot-melt self-leveling adhesive layer is 65-80℃, the penetration at 25℃ is 80-110 / 0.1mm, the melt viscosity at 160℃ is ≤400 mPa·s, and the melt viscosity at 180℃ is ≤200 mPa·s.

2. The bridge deck waterproof and crack-resistant tape according to claim 1, characterized in that, Based on the total mass of material A forming the functional rubber layer, material A contains: 40-50 wt% of 90# petroleum asphalt, 6-10 wt% of star-shaped SBS, 14-25 wt% of softening oil, and 4-10 wt% of rubber powder. Preferably, based on the total mass of material A forming the functional adhesive layer, material A further contains: 1-3 wt% acid-base buffer, 2-5 wt% chloride ion scavenger, 0.3-0.6 wt% coupling agent, 0.3-0.5 wt% antioxidant, and 10-18 wt% inorganic filler.

3. The bridge deck waterproof and crack-resistant tape according to claim 2, characterized in that, The acid-base buffer is selected from at least one of cobalt borate and cobalt naphthenate. And / or, the chloride ion scavenger is selected from at least one of magnesium aluminum layered bimetallic hydroxide, calcium aluminum layered bimetallic hydroxide, and synthetic zeolite; And / or, the coupling agent is selected from at least one of silane coupling agent KH-550, silane coupling agent KH-560, and titanate coupling agent.

4. The bridge deck waterproof and crack-resistant tape according to claim 1, characterized in that, Based on the total mass of material B forming the hot melt self-leveling compound layer, material B contains: 45-55 wt% of 70# petroleum asphalt, 2-7 wt% of linear SBS, 18-30 wt% of softening oil, and 3-6 wt% of rubber powder. Preferably, based on the total mass of material B forming the hot melt self-leveling adhesive layer, material B further contains: 2-5 wt% thickener, 3-8 wt% binder, 0.3-0.5 wt% antioxidant, and 5-12 wt% inorganic filler.

5. The bridge deck waterproof and crack-resistant tape according to claim 4, characterized in that, The thickener is selected from at least one of microcrystalline wax, Fischer-Tropsch wax, and polyethylene wax; And / or, the adhesive is selected from at least one of C5-C9 copolymer petroleum resin, hydrogenated terpene resin, and rosin resin.

6. The bridge deck waterproof and crack-resistant tape according to claim 1, characterized in that, Based on the total mass of material C forming the aging-resistant rubber layer, material C contains: 50-63 wt% of 90# petroleum asphalt, 8-15 wt% of linear SBS, 7-14 wt% of softening oil, and 10-18 wt% of rubber powder. And / or, based on the total mass of material C forming the aging-resistant adhesive layer, material C further contains: 0.2-0.6 wt% of ultraviolet absorber, 0.3-0.8 wt% of antioxidant, and 1-4 wt% of inorganic filler; And / or, the ultraviolet absorber is selected from at least one of UV-326 and UV-328.

7. The bridge deck waterproof and crack-resistant tape according to any one of claims 1-6, characterized in that, The softening oil is selected from at least one of aromatic oils and naphthenic oils; And / or, the average particle diameter of the adhesive powder is ≤180μm.

8. The bridge deck waterproof and crack-resistant tape according to any one of claims 1-6, characterized in that, The antioxidant is selected from at least one of antioxidant 1010 and antioxidant 1076; And / or, the inorganic filler is selected from at least one of nano-calcium carbonate and carbon black N330.

9. The bridge deck waterproof and crack-resistant tape according to any one of claims 1-6, characterized in that, The surface of the core adhesive layer is covered with a polyethylene film layer.

10. A construction method for the bridge deck waterproof and crack-resistant adhesive tape according to any one of claims 1-9, characterized in that, The method includes: Step 1: Lay the bridge deck waterproof and crack-resistant tape on the bridge deck. Use a flame torch to heat the lower surface of the bridge deck waterproof and crack-resistant tape, so that the hot melt self-leveling adhesive layer on the lower surface is heated to 140-160℃ and melts into a liquid state. While it is hot, use a pressure roller to roll it, so that the adhesive of the hot melt self-leveling adhesive layer on the lower surface actively flows into the micro-cracks of the base surface under pressure. Step 2: Pour heated asphalt mixture onto the upper surface of the bridge deck waterproof and crack-resistant tape to melt the aging-resistant adhesive layer on the upper surface of the tape. Step 3: Use a road roller to compact and shape the material, so that the aging-resistant rubber layer on the upper surface of the bridge deck waterproof and crack-resistant tape is fused with the heated asphalt mixture. After cooling and setting, the construction is completed.